The Epistemology of Qur'anic Huda (Guidance): Assessing the Validity of the Qur'anic Maqasid - Firdaus; Juraidi (AN NUR: Jurnal Studi Islam, 2026)
This study examines the epistemology of the Qur'anic Huda as a methodological framework for discovering the validity of the maqasid of the Qur'an. Using a qualitative method with a library approach, this study analyzes the concept of Huda and its derivations in the Qur'an and explores its epistemological structure that integrates reason, heart, senses, and revelation. The results of the study indicate that the epistemology of Huda has a dynamic gradation of knowledge and offers three epistemological criteria for testing the validity of maqasid, namely textual coherence, conformity with the purpose of creation, and transformative impact. This study reconstructs the maqasid of the Qur'an in three main pillars: tazkiyah (self-purification), 'adalah (justice), and 'imarah (prosperity), which are proven to be more comprehensive and responsive to contemporary challenges. The epistemology of Huda has significant implications for the development of an interpretation methodology that is maqasidiy, integrative, and ethical-transformative, making the Qur'an an actual and relevant guide for human life.